“Maybe We Should Destigmatize It”: Young Adults’ Perceptions about Instruction on Sexual Consent and Sexual Coercion During Adolescence - Summers, Monica; Van Camp, Tinneke (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: For decades, scholars and sexual health professionals have urged policymakers to improve the efficacy of sex education. Although some progress has been made through the development of comprehensive sexuality education (CSE), curricula in the United States remain limited. For instance, healthy sexual encounters require mutual sexual consent, void of sexually coercive behaviours, yet CSE initiatives only recently added instruction on consent and coercion as important parts of sex education curricula. Further, little is known about what youth learn about consent and coercion through family, friends, and media. The purpose of this study, then, was to gain insight into the information young adults received during adolescence about sexual consent and coercion through formal and informal sources, and to seek their perceptions about possible curriculum improvement. Methods: This study utilized five focus groups to assess 32 college students’ perceptions about their adolescent experiences with instruction on consent and coercion in formal and informal sex education. The mean participant age was 22, and most were women, heterosexual, and Latinx. Results: The results indicated that these young adults did not learn about sexual consent and coercion while in high school, but believed that these topics should have been addressed. They also believed that formal sex education should move away from abstinence-only or abstinence-forward education, and should not be rooted in fear-mongering. Gender impacted whether and what youth learned about sexual consent from parents and peers. While mothers talked to sons about using contraceptives and also about obtaining consent, they talked to daughters about negative sex outcomes, such as a ruined reputation or early pregnancy. Fathers were less likely to talk to their children about sex, especially daughters. Young men talked to peers about whether they had sex, while young women talked to their friends about the physical experience of having sex. Implications: Implications support the implementation of sex education in high schools that facilitates not only physically safe, but also emotionally healthy relationships, as well as an urgency for a cultural shift towards the acknowledgment of intimate behaviours as normative processes among adolescents.